MOR2 organization profile survey data - Fernández-Giménez, M. E; Ulambayar, Tungalag; Baival, Batkhishig; Batjav, Batbuyan; Laituri, Melinda; Linn, Sophia; Roynane, Bridget; Holfelder, Kirsten; Jamiyansharav, Khishigbayar (Colorado State University. Libraries, 2020)
Organization level social data were collected from 142 pastoral groups.
Those listed as authors substantially designed instruments and data collection protocols, directly supervised data collection and collected data, designed database, and oversaw data entry and quality checking.
Additional acknowledgements (people listed assisted with field data collection, data entry, and establishment of on-line data archive): The following individuals helped with data collection or data entry in Mongolia: Amanguli, Ariuntuya, Azjargal J., Battuul B., Enkhmunkh B., Erdenechimeg B., Gantsetseg A., Narantuya N., Nomin-Erdene B., Odgarav J., Pagmajav D., Solongo Ts., Tamir L., Unurzul A., Uuganbayar B., Vandandorj S. The following individuals guided establishment of on-line data archive at Colorado State University: Tobin Magle, Mara Sedlins, Daniel Draper.
Warner College of Natural Resources
Keywords: Mongolia; community group; survey